Pengembangan SIUJUNKAN Berbasis Pembelajaran Penemuan pada Materi Siklus Air untuk Meningkatkan HOTS Siswa Sekolah Dasar - Damayanti, Frianka Ivana; Murni, Cahya Intan; Pramudyanti, Pramudyanti; Dewi, Pramita Sylvia (STKIP PGRI Bandar Lampung, 2024)
This research aims to develop student worksheets (LKPD) based on discovery learning in learning rain cycle material and measuring students' high order thinking skills. The discovery learning method allows students to actively explore concepts and connect information from various sources, so it is hoped that they can improve their critical thinking skills. The LKPD developed will include exploration, observation and reflection activities that will enable students to identify rain cycles. In addition, the HOTS measurement instrument will be used by students before and after using the LKPD. It is hoped that the results of this research can contribute to the development of more effective science learning and increase student HOTS. By understanding how discovery learning can influence HOTS abilities, educators can design learning strategies that are better and relevant to students' needs